(untitled) (Al-Farooq Journal of Sciences, 2026)
In recent years, interest has grown in the concept of green education as a modern approach to supporting sustainable development, given its role in promoting environmental awareness and establishing educational practices related to conserving natural resources and improving quality of life. This seminar examines the reality of green education in Libya by analyzing the level of integration of environmental sustainability concepts within educational institutions, focusing on the most prominent challenges hindering the transition to a more sustainable education system. The seminar aims to highlight the importance of green education in supporting sustainable development ,the study analyzes the reality of its implementation in the Libyan educational environment, in addition to identifying the economic, administrative, technical, and cultural obstacles facing educational institutions. It also seeks to present a set of mechanisms and proposals that can contribute to the development of green education and enhance its role in building a society more aware of environmental and developmental issues. The symposium adopted a descriptive-analytical approach, reviewing literature, previous studies, and reports related to green education and sustainable development. It concluded that implementing green education in Libya still faces numerous challenges, including weak educational infrastructure, limited training programs, and the incomplete integration of sustainability concepts into curricula. However, the symposium also noted the existence of genuine opportunities to develop this field through updating educational policies, strengthening institutional partnerships, and promoting environmental awareness within society.